Peran Non-State Actor dalam Penanganan dan Pencegahan Kasus Lesbian, Gay, Biseksual, dan Transgender (LGBT) di Kota Bukittinggi - Ravianda, Giva; Sasmita, Siska (Al-DYAS, 2025)
The phenomenon of LGBT in Bukittinggi City has shown a significant increase in recent years, with the number of recorded cases rising from 56 individuals in 2023 to 272 in 2024. This situation has prompted the involvement of the Masyarakat Hukum Adat Kurai (Kurai Customary Law Community) as a non-state actor in efforts to address and prevent LGBT-related behaviors in the region. This study aims to analyze the role of the Masyarakat Hukum Adat Kurai as a non-state actor in handling and preventing LGBT cases in Bukittinggi City, as well as to identify the supporting and inhibiting factors. A descriptive qualitative method was used, with data collected through interviews and document analysis. The findings reveal that the Masyarakat Hukum Adat Kurai performs three main roles. First, in policy-making, they initiated the customary sanction dibuang sepanjang adat, proposed village regulations concerning social deviance, and implemented a barcode system in boarding houses. Second, in the development and implementation of government policies, they lobbied for policy ratification and participated in PKBAM and PUPB programs. Third, in collaboration with state actors, there exists a relationship of mutual dependence: the Masyarakat Hukum Adat Kurai relies on government funding, while the government depends on customary law as a cultural solution to LGBT cases. Supporting factors include multi-stakeholder support, integrated institutional coordination, strong cultural legitimacy, and adequate infrastructure and human resources. The main inhibiting factor is budgetary limitation.